Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Functional traits mediate the resistance and resilience of sap-flux density in response to drought stress - Yanting Hu; Karina V.R. Schäfer; Chuan Yuan; Yunpeng Nie; Liwei Zhu; Yelin Zeng; Shuai Ouyang; Liang Chen; Pifeng Lei; Xiangwen Deng; Xi Fang; Wenhua Xiang (Agricultural and Forest Meteorology, 2026)

Species identity outweighs richness in shaping soil microbial resource limitation in subtropical mixed Pinus massoniana-broadleaved plantations - Yi Li; Xi Fang; Wenhua Xiang; Pifeng Lei; Liang Chen; Shuai Ouyang; Xiangwen Deng; Yanting Hu; Huili Wu (CATENA, 2026)

Mycorrhizal Type Defines Priming Effects in Organic and Mineral Forest Soils - Xionghui Liu; Liang Chen; Wenhua Xiang; Shuai Ouyang; Huili Wu; Yanting Hu; Pifeng Lei; Xiangwen Deng; Xi Fang; Biao Zhu; Yakov Kuzyakov (Global Change Biology, 2026)
Trees associated with arbuscular mycorrhizal (AM) or ectomycorrhizal (ECM) fungi create distinct soil environments that influence organic matter accumulation, decomposition, and persistence. As forest composition changes globally, understanding how shifts in mycorrhizal dominance affect soil carbon (C) cycling becomes increasingly important. Priming effects, where fresh C inputs alter the decomposition of existing soil organic matter, represent a critical but poorly understood mechanism, through which tree mycorrhizal associations may regulate soil C storage and loss. To address the role of mycorrhizal associations in regulating priming effects, we collected soils from forest plots differing in their dominance of mycorrhizal‐associated tree types in a subtropical forest and quantified priming effects with 13 C‐labeled glucose. In the organic topsoil, priming effects were positive, but strongly decreased (from 19 to 2.3 μg C g −1 soil after 28 days of incubation) as ECM trees became more dominant. This reduction was linked to higher particulate organic carbon, a greater fungal‐to‐bacterial ratio, and more genes for degrading recalcitrant C. Conversely, in the mineral subsoil, priming effects were generally negative, with AM‐dominated plots (−14 μg C g −1 soil) showing stronger negative priming than in ECM‐dominated plots (−3.2 μg C g −1 soil after 28 days of incubation). This is primarily because AM dominated soils have greater availability of mineral‐associated organic matter and nitrate content, as well as higher microbial carbon use efficiency. Tree mycorrhizal associations thus regulate priming effects through depth‐dependent changes in C stability, nitrogen availability, and microbial functional activity. We conclude that forecasting forest C dynamics in response to mycorrhizal compositional shifts must account for these soil depth‐specific mechanisms.

Corrigendum to “Woody species with higher hydraulic efficiency or lower photosynthetic capacity discriminate more against 13C at the global scale” [Science of the Total Environment, 908 (2024), 168172] - Yanting Hu; Karina V.R. Schäfer; Songjiang Hu; Yelin Zeng; Shuai Ouyang; Liang Chen; Pifeng Lei; Xiangwen Deng; Zhonghui Zhao; Xi Fang; Wenhua Xiang (Science of The Total Environment, 2026)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

A large-scale integrated transcriptomic atlas for soybean organ development - Jingwei Fan; Yanting Shen; Chuan Chen; Xi Chen; Xiaoyue Yang; Haixia Liu; Ruiying Chen; Shulin Liu; Bohan Zhang; Min Zhang; Guoan Zhou; Yu Wang; et al. (Molecular Plant, 2025)

Hydraulic traits exert greater limitations on tree-level maximum sap flux density than photosynthetic ability: Global evidence - Yanting Hu; Liwei Zhu; Chuan Yuan; Wenneng Zhou; Yelin Zeng; Shuai Ouyang; Liang Chen; Huili Wu; Pifeng Lei; Xiangwen Deng; Zhonghui Zhao; Xi Fang; et al. (Science of The Total Environment, 2024)

Toxic mechanisms of the antiviral drug arbidol on microalgae in algal bloom water at transcriptomic level - Ziwei Guo; Huan He; Kunqian Liu; Zihui Li; Yanting Xi; Zhicheng Liao; Guohua Dao; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2024)

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

The environmental risks of antiviral drug arbidol in eutrophic lake: Interactions with Microcystis aeruginosa - Ziwei Guo; Huan He; Gui Yang; Kunqian Liu; Yanting Xi; Zihui Li; Yu Luo; Zhicheng Liao; Guohua Dao; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2024)

Woody species with higher hydraulic efficiency or lower photosynthetic capacity discriminate more against 13C at the global scale - Yanting Hu; Karina V.R. Schäfer; Songjiang Hu; Wenneng Zhou; Dong Xiang; Yelin Zeng; Shuai Ouyang; Liang Chen; Pifeng Lei; Xiangwen Deng; Zhonghui Zhao; Xi Fang; et al. (Science of The Total Environment, 2024)

A non-uniform pressure distribution model on the end face in screw expander and shaft seal leakage characteristicsfrEtude des paramètres de la Structure sur les fuites d'arbres dans un expandeur à vis basé sur un nouveau modèle de distribution de pression non uniforme sur la face d'extrémité - Yafen Tian; Zebin Wang; Yanting Geng; Xi Chen; Hua Zhang; Qize He (International Journal of Refrigeration, 2023)

Tree-level stomatal regulation is more closely related to xylem hydraulic traits than to leaf photosynthetic traits across diverse tree species - Yanting Hu; Zhihui Sun; Yelin Zeng; Shuai Ouyang; Liang Chen; Pifeng Lei; Xiangwen Deng; Zhonghui Zhao; Xi Fang; Wenhua Xiang (Agricultural and Forest Meteorology, 2023)

Metabolomics analysis of the potential toxicological mechanisms of diquat dibromide herbicide in adult zebrafish (Danio rerio) liver - Ye Xiao; Xiang Lin; Meilan Zhou; Tianyu Ren; Ruili Gao; Zhongqun Liu; Wenjing Shen; Rong Wang; Xi Xie; Yanting Song; Wenting Hu (Fish Physiology and Biochemistry, 2022)

The complete plastome of Nyssa yunnanensis, a critically endangered tree species - Xuchen Yang; Yanting Yang; Minghui Kang; Xinyi Guo; Tao Ma; Zhenxiang Xi (Conservation Genetics Resources, 2019)